1997
DOI: 10.1021/ja972158y
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular β-Sheet Stabilization with Aminopyrazoles

Abstract: 3-Aminopyrazole derivatives are the first artificial templates that stabilize the β-sheet conformation in N/C-protected dipeptides by purely intermolecular interactions. In the complex two aminopyrazole molecules lie exactly above and below the peptide backbone. Binding to the top face of the peptide is strongly favored because it forms three cooperative hydrogen bonds simultaneously to the receptor molecule, whereas the bottom face has only two. Polymerizable 3-amino- and 3-amidopyrazoles have been made acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
1
4

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 47 publications
4
31
1
4
Order By: Relevance
“…Compound 1 crystallized as monoclinic in the space group P2 1 /n, aϭ8.227 (2) Å, bϭ8.283(1) Å, cϭ11.111(2 Ethyl 1-Acetyl-3-amino-1H-pyrazole-4-carboxylate (2) To a suspension of 1 (775 mg, 5 mmol) and DMAP (121 mg, 1 mol) in DMF (0.5 ml) was added Ac 2 O (0.71 ml, 7.5 mmol), after 1 h at room temperature a white precipitate was filtered off and washed with DMF (1 ml) to furnish 2 (550 mg, 56% isolated yield), mp 110°C; TLC: Rf 0.86; HPLC: t R 3.0 min, 99% purity; 1 H-NMR (DMSO-d 6 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 1 crystallized as monoclinic in the space group P2 1 /n, aϭ8.227 (2) Å, bϭ8.283(1) Å, cϭ11.111(2 Ethyl 1-Acetyl-3-amino-1H-pyrazole-4-carboxylate (2) To a suspension of 1 (775 mg, 5 mmol) and DMAP (121 mg, 1 mol) in DMF (0.5 ml) was added Ac 2 O (0.71 ml, 7.5 mmol), after 1 h at room temperature a white precipitate was filtered off and washed with DMF (1 ml) to furnish 2 (550 mg, 56% isolated yield), mp 110°C; TLC: Rf 0.86; HPLC: t R 3.0 min, 99% purity; 1 H-NMR (DMSO-d 6 …”
Section: Methodsmentioning
confidence: 99%
“…In order to determine the position of hydrogen at nitrogen atoms in compounds 1 and 5 in solution we performed NMR analysis and calculations. Compound 1 in the CDCl 3 and DMSO-d 6 solutions is a mixture of tautomers, according to NOESY, multinuclear HMBC and HSQC spectra and as well as calculations (Table 3). In addition, it was shown that 5 in DMSO-d 6 contains a mixture of tautomers which was corroborated by calculations ( Table 3).…”
mentioning
confidence: 99%
“…The assignment of amide NH protons is shown in Scheme 2 and the result of the VT 1 H NMR is summarized in Table 3 (see Supporting information for plots of chemical shifts versus temperature). The amide protons that are involved in intramolecular or intermolecular hydrogen bonding experience temperature dependent chemical shifts [25]. For example, the temperature coefficients of compound 1 (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Diese starren Heterocyclen wurden in Lösung auf ihre Fähigkeit zur Erkennung des Peptidrückgrats mit NMR-und IR-spektroskopischen Methoden sowie mit Kraftfeldrechnungen untersucht. [4][5][6][7][8] Um mit einer möglichen Peptiddimerisierung konkurrieren zu können, muss mit der Bildung eines Peptid- Ein entscheidender Vorteil der Molekularstrahlexperimente besteht in der Möglichkeit, isolierte Cluster massen-, isomeren-und zustandsselektiv zu analysieren. Die R2PI-Methode (R2PI: resonance enhanced two photon ionization), [9] bei der das Molekül durch ein UV-Photon zunächst angeregt und anschließend durch ein zweites UV-Photon ionisiert wird, ermöglicht eine Diskriminierung auch zwischen einander sehr ähnlichen Isomeren, z.…”
unclassified